Lightning Induced Ocular Complications: A Case Report - Chakraborti, Chandana (Pakistan Journal of Ophthalmology, 2018)
Lightning injuries range from various forms of transient focal damage to instant death. Eye injuries from lightning are not uncommon. We report a case of lightning injury in a 30 – year old female who presented to us one month after the injury. On examination her best corrected visual acuity (BCVA) was 6/24 in right eye (RE) and 6/60 in left eye (LE). Slit lamp biomicroscopy revealed anisocoria, bilateral uveitis and sphincter tear in left eye. There was lightning induced cataract in both eye and macular hole in left eye. Optical Coherence Tomography (OCT) revealed macular cyst in right eye (RE) and a full thickness macular hole (FTMH) in left eye. Patient was treated with topical corticosteroid and cycloplegics in both the eyes. At subsequent follow up cataract surgery was done in both eyes (BE). Post-operative best corrected visual acuity at 1 month was 6/9 and 6/12 in right and left eye. There was a spontaneous resolution of the macular lesion in both eyes.